A comparative reappraisal of debt relief measures for natural person debtors in South Africa - Coetzee, Hermie (University of Pretoria, 2015)
The purpose of this thesis is to do a comparative reappraisal of debt relief measures available to natural person debtors in the South African insolvency law. Although the broader South African natural person insolvency system currently includes three statutory debt relief procedures, namely, the sequestration procedure regulated by the Insolvency Act 24 of 1936, the administration order procedure in terms of the Magistrates Courts Act 32 of 1944 and the debt review procedure found in the National Credit Act 34 of 2005, not all natural person debtors have access to the system. The majority of this marginalised group are debtors with no income and no assets (the so-called No Income No Asset (NINA) debtors). Also, only one measure provides real debt relief in the form of a statutory discharge of debt. Furthermore, the existing measures have developed in a haphazard fashion which has led to a multiplicity of procedures, regulators and forums that resulted in ineffectiveness, inequality and uncertainty. The larger system therefore lacks proper policy considerations. This thesis provides the reasons for reform by, amongst others, arguing that the present situation is unconstitutional as it unreasonably and unfairly discriminates against the NINA group of debtors in particular. It measures the broader South African system against internationally accepted principles of efficient and effective natural person insolvency regimes. In this regard it is found that the system as a whole is seriously deficient. With reference to international principles and guidelines as well as suitable attributes found in foreign jurisdictions, the thesis concludes with suggestions for real law reform. Both substantive and procedural recommendations are made.
URI: https://repository.up.ac.za/handle/2263/52372

A Comparative Study on Customs Tariff Classification - Colesky, Theo (University of Pretoria, 2015)
The field of customs is commonly referred to as that of imports and exports. It is perceived as a maze of processes, procedures, and forms required to enable a customs administration to perform their wide range of responsibilities. One of the responsibilities of a customs administration is the collection of duties, which necessitates classification of the goods in question. This study sets out to determine the extent of customs control in relation to tariff classification in South Africa. The starting point is the establishment of the foundations of customs, both internationally and in South Africa. After origin and valuation, tariff classification is the third technical customs-related focus area. An analysis of the responsibilities of the customs administration in South Africa confirms the importance of revenue collection and, subsequently, tariff classification. As a result of South Africa’s membership of the World Customs Organization, specific obligations in relation to tariff classification are incurred. The implementation and application of the international provisions are considered and compared in South Africa, Australia, and Canada. Not only is South Africa’s existing legislation considered, but also two new Acts. It is found that despite similarities in the implementation of the Harmonized System Convention into the legislation of the three countries, South Africa’s existing legislation makes the most detailed provision for the Harmonized System and its aids. This is based on the finding that the legislation in Australia and Canada, as well as the two new Acts in South Africa, do not have the same comprehensive provisions. A critical review of the varying processes of classification in the three countries suggests that more suitable and effective processes could be implemented in South Africa. In addition, a synopsis of some of the principles developed in case law is provided and compared. In relation to facilitation, the access to relevant information and the adequacy thereof, as well as the availability of rulings, are considered. Differences in the approach to dispute resolution in the three countries are furthermore provided. Proposals are made to address the discrepancies in the implementation and application of the legislation, the process of classification, the principles developed in case law, the enhancement of related guides, the publication of tariff classification rulings, and the extent of facilitation and dispute resolution. Finally it is recommended that an independent and expert tribunal is established to adjudicate technical customs matters.
URI: https://repository.up.ac.za/handle/2263/42838
Keywords: Comparative study; Customs tariff classification

The Disclosure and Use of Social and Environmental Information by Libyan Banks - Elsakit, Omer M (Griffith University, 2015)
There is increasing interest in social and environmental issues throughout the world, especially in developed countries, where governments, organizations, and society well recognise the impact of business activities on the environment and society. Consequently, companies have potentially no alternative but to behave in a responsible manner, socially and environmentally, and to prove this by disclosing information about their related conduct. In this regard, banks play two important roles: first, as providers of social and environmental information in much the same manner as nonfinancial companies; and second, as providers of finance, by encouraging—if not obliging—bank customers to consider society and the environment in their bank-financed projects. Banks fulfil the latter role by requiring social and environmental information from companies when making lending decisions. Only a few Libyan studies have examined social and environmental issues in relation to economic activity, and these have generally revealed low levels of disclosure practice by organisations, including banks, in these areas. In addition, many changes have taken place in the Libyan economy and banking sector in recent years, including the establishment of a market exchange; decreased government participation in economic activities; and increased growth of the private sector that results, especially in the banking sector, with the entrance of foreign investors. These changes have placed a new emphasis on bank operations and the participation of banks in the Libyan economy. Thus, studying Libyan banks, in terms of their role in the environment and society, has attracted growing interest. As such, the core objective of this thesis has been to investigate the position of Libyan banks in relation to social and environmental issues and disclosure by considering their dual role as both providers and users of such information.
Keywords: Banks and banking; Environmental policy; Finance and environment; Libya

International taxation of cross-border digital commerce - Kadikov, Artem (University of Oxford, 2015)
This thesis discusses jurisdiction to tax cross-border digital commerce. The primary objective is to consider the reasons for the erosion of jurisdictional links, or nexus, between countries and taxpayers' digital activities and evaluate possible solutions for addressing such nexus erosion. Whilst it is argued that digital commerce is impossible to ring-fence due to digital technologies transcending all industries, the main focus of this research is on automated business models as case studies for the broader tax issues applicable across the entire digital economy. Using cloud computing, online advertising and e-tailing models as examples of digital commerce in the narrow sense, this thesis demonstrates that the proxies for establishing jurisdictional nexus have become increasingly fluid, thereby challenging the traditional international tax regimes for profits and consumption taxation. Numerous policy solutions have been proposed in order to rectify nexus erosion, including global and territorial tax models. Unlike the previous research in this area, this thesis focuses on the nexus elements of such proposals and assesses their viability in the light of the wider Internet governance jurisprudence. Global tax solutions, such as global e-commerce taxes and formulary apportionment, are analysed in the context of the international governance regime for the technical Internet infrastructure. Territorial virtual tax solutions, such as virtual permanent establishments, withholding taxes and destination cash flow taxes, are considered in the light of the Internet jurisprudence on the 'effects' and 'targeting' nexus standards. It is argued that, given the lack of technical and political infrastructure, none of the proposed routes would be viable from a practical perspective in the near future. It is concluded, therefore, that a practical solution would involve retaining the traditional profits and consumption tax models, whilst testing a narrow version of the digital targeting nexus standard as a backstop anti-abuse measure. It is envisaged that the limited anti-avoidance provision would subsequently pave the way for a comprehensive long-term solution, as digitisation continues to transform global commerce.
Keywords: Corporations; Digital commerce taxation; Double taxation; E-commerce taxation; Electronic commerce; International Trade; International business enterprises; Internet governance; Internet jurisdiction; Internet taxation; Jurisdiction to tax; Taxation

Establishing continental sovereignty in Africa: risk and opportunity in financial integration - lessons for Africa from a legal perspective - Ngwafor Ndeh, Edwin (University of Glasgow, 2015)
This thesis identifies and defines the new African sovereignty. It establishes a modern sovereignty in Africa hatched from the changing nature of sovereignty in which countries come together at various levels or grades of partial surrender of national sovereignty in order to work closer together for their mutual advantage and benefit. To this end, the narrative zooms in on the central issues within the realms of money matters whereby a new model of monetary sovereignty and monetary solutions is designed in an attempt to ease the recurring tensions and challenges of modern national sovereignty in the continent of Africa. As such, this discussion will offer a historical journey through the constitution of sovereignty, to the birth of the nation state and international public law. It develops the theory of the changing nature of sovereignty within the modern state and opens new lines of inquiry for Africa. In this regard, it draws from juxtaposing and mixing elements of regional and global financial integration as well as retaining national financial sovereignty features to form this new design which I dub continental sovereignty. At its core, the thesis will deal with the legal aspects that stem from the co-mingling of legal systems of nation states and communities at the regional and global levels within the context of financial integration. The argument is that the rule of law remains sacrosanct in monetary management. Effective financial integration is the result of properly structured and managed legal frameworks with robust laws and institutions whether at a national, regional or global level. However, the thesis reveals that in order to avoid undermining the progress of Africa’s financial integration project, any solution for Africa must be immersed within a broader global solution where development issues are addressed and resolved and Africa can form a more central part in all relevant international discussion fora. The work will expound these issues by applying them within a regional and global context, with the state of affairs in Africa forming the nucleus. This application consequently presents the six key themes of the thesis which will be considered therein. They are: a.) regional advantage: which exploits the possibilities of deeper and further financial integration between smaller communal arrangements; b.) regional risk and exposure: the extent to which this deeper form of financial integration can spiral out of control if effected too quickly and too ambitiously; c.) global advantage: which considers the merits of global financial integration and the influence exerted by financial laws on the global financial architecture; d.) global risk and exposure: which considers the challenges of global financial integration especially within the background of the Global Financial Crisis 2007-2008; e.) African challenge: which considers the extent to which this analysis impacts the African economic and financial integration agenda; and f.) development challenge: which examines the extent to which global development issues impact the African solution (continental sovereignty) and the need for any solution for the continent to be roped into a broader global solution within which Africa can form an important part. Even though the thesis requests an optimistic undertone on the progress made so far, it unearths the African problem of multiple national sovereignty and multiple overlapping regional sovereignty constituted as the ‘spaghetti bowl’ dilemma. As such, the unique contribution to knowledge on financial integration in Africa can be echoed in these words: Africa‘s financial integration agenda has had little success in authenticating a systematic and dependable legal framework for monetary management. Efforts made have been incomplete, substandard, and not carefully followed through particularly reflected in the impuissant nature of the judicial enforcement mechanisms. Thus, the thesis argues that, any meaningful answer to the problems dogging the continent is inter alia deeply entrenched within a new form of cooperative monetary sovereignty. In other words, the thesis does not prescribe the creation of new laws; rather it advocates the effective enforcement of existing laws.
Keywords: African Integration Project; Crisis response; Financial crisis; Financial integration; Regional systems; Regulation of financial markets; continental sovereignty

Internal Audit Characteristics and Quality of Accounting Information in Nigeria - Ogundana, Oyebisi Mary; Ojeka, Stephen; Ojua, Michael; Nwaze, Chukwu (Conference Proceedings, 2015)
The basic goal of Accounting is to provide enabling accounting information for reliable decision-making. The quality level of this accounting information comes from the company's governance practices, thereby emphasizing the importance of corporate governance in companies. Recently, following the financial crises resulting in accounting scandals, attention has been moving towards Internal Audit Function as an important factor in the structure of Corporate Governance. This paper therefore examined the extent of the relationship between internal audit function and the quality of accounting information of companies. The study adopted the Survey research design. The research instrument employed was Questionnaire which was administered to internal auditors of the “Big Four”. Linear regression analysis was employed in the analysis of the data collected with the use of Statistical Packages for Social Sciences (SPSS). The results revealed that there is a significant relationship between the internal audit characteristics and the quality of accounting information. It was recommended that in order to provide credibility to the financial statement, there should be a law in place mandating attachment of internal auditors report to the financial statement
Keywords: Accounting quality; Accounting report; Corporate governance; Fraud; internal auditing

Synthetic securitisation in South African law - Wessels, Francois Claassens (University of Pretoria, 2015)
The objective of this thesis is to critically analyse synthetic securitisation schemes in South African law as synthetic collateralised debt obligations using primarily credit default swaps (CDSs). This transpires from the perspective of primarily company law, and secondarily securities law and the law of contract. It includes a contextualised study of these schemes with regards to their origins, their significance regarding the recent financial crisis, and their rationales micro-economic influence and Basel capital requirements. Not only are the participants, such as parties acting in a primary role and secondary role and special-purpose institutions, studied, but also the obligations between these parties, such as the CDS contract, and the meaning of commercial paper, the legal nature of credit-linked notes, the business of a bank, and the influence of recent case law. It also includes a consideration of synthetic securitisation schemes in terms of the Collective Investment Schemes Control Act 45 of 2002. Furthermore, the role of systemic risk and moral hazard is explained, as well as the interaction between synthetic securitisation schemes, credit rating agencies and the function of risk management. The CDS is compared with insurance contracts, and a discussion of the 2014 International Swaps and Derivatives Association Credit Derivative Definitions is incorporated. For legal comparison, the South African model is compared with Canadian law and its unfunded credit derivatives in the light of recent regulation, and compared to German law and its prevalence of funded credit derivatives. Finally, suggestions are made as to the future of synthetic securitisation schemes.
URI: https://repository.up.ac.za/handle/2263/53208
Keywords: Company law; Debt obligation; Securities Law; Securitisation; South Africa; Titrisation